Highly conductive, ultra-flexible and continuously processable PEDOT:PSS fibers with high thermoelectric properties for wearable energy harvesting. (December 2020) - Wen, Ningxuan; Fan, Zeng; Yang, Shuaitao; Zhao, Yongpeng; Cong, Tianze; Xu, Shihong; Zhang, Hao; Wang, Jianzhen; Huang, Hui; Li, Chengwei; Pan, Lujun
Abstract: Conducting polymers, particularly poly (3, 4-ethylenedioxythiophene): poly (styrenesulfonate) (PEDOT:PSS), have been intensively studied for thermoelectric (TE) applications, owing to their unique advantages including nontoxicity, low cost, good mechanical flexibility and low thermal conductivity. The TE properties of the conducting polymers show a strong dependence on their polymer chain conformations and chain stacking structures. In this work, one-dimensional PEDOT:PSS fibers were developed to improve the chain packing order and increase the proportions of quinoid PEDOT by the spatial confinement effect arising from the specific fiber configuration. The PEDOT:PSS fibers were produced through a continuous wet-spinning process followed by a one-step treatment with sulfuric acid. The optimized PEDOT:PSS fibers achieved a power factor of 147.8 μW m −1  K −2 with an electrical conductivity of 4029.5 S cm −1 and a Seebeck coefficient of 19.2 μV K −1 at room temperature. The power factor was 15 times that of a two-dimensional PEDOT:PSS film processed at the same condition. Besides, the PEDOT:PSS fibers also exhibited a high tensile strength of 389.5 MPa and a large breaking strain of 30.5%. Based on the PEDOT:PSS fibers, a prototype fibrous TE generator (TEG) was assembled. The fibrous TEG delivered an output power density of ~0.273 μW cm −2 using the human body heat. This work paves the way to developing high-performance organic TE materials by approaches of polymer chain modulation. Graphical abstract: Image 1 Highlights: PEDOT:PSS fibers were produced via wet-spinning followed by acid treatment. Power factor of the PEDOT:PSS fibers was 15 times that of a film counterpart. The PEDOT:PSS fibers had a high strength, large breaking strain and high toughness. The fiber configuration results in high degree of quinoid-PEDOT packing alignment. The practical application of the fibrous TEG as a wearable device was demonstrated.